n-Hexane isomerization on Ni-Pt catalysts/supported on HUSY zeolite: The influence from a metal content - Yoshioka, Carlos M.N. (2005)
Bi-functional catalysts were prepared to contain Ni, Pt or both, supported on a HUSY zeolite, with the following metal contents: catalysts 30, 130 and 180 × 10-6 atg metal/g catalyst. These catalysts resulted from a competitive ion exchange with the use of aqueous solutions from [Ni(NH 3)6]Cl2 and [Pt(NH3) 4]Cl2 complexes. The catalysts were provided with a scheduled temperature reduction (TPR) and subjected to a catalytic assessment on the n-hexane isomerization at 250 °C and 1 atm. TPR results showed larger reducibility of Ni+2 cations in the presence of Pt. Bi-metallic Ni-Pt catalysts showed to have smaller deactivation and much higher activity compared to monometallic Ni catalysts. The selectivity for the production of di-ramified alkanes increases as the Ni content increases.